BREACH OF THE IMPLIED DUTY TO PRESERVE MUTUAL TRUST AND CONFIDENCE IN AN EMPLOYMENT RELATIONSHIP: A CASE STUDY OF Moyo v Old Mutual Limited (22791/2019) [2019] ZAGPJHC 229 (30 July 2019) - Konanani Happy Raligilia; Kodisang Mpho Bokaba (Obiter, 2021)
This case note is intended to revisit the contentious aspect of the implied duties of South African labour law in the individual employment relationship. Significantly, the case note intends to remind the reader about the importance of adhering to certain implied duties in the contract of employment. In this regard, the implied duty to preserve mutual trust and confidence is the central theme of this case note. On the one hand, the implied duty to safeguard mutual trust and confidence imposes an obligation upon the employer to conduct itself in a manner not likely to destroy, jeopardise, or seriously damage the trust relationship and confidence in the employment relationship. On the other hand, this implied duty is becoming a significant yardstick used by employers to address contractual labour disputes in South Africa. In order for an employer to invoke this implied duty, it must be expected that the employee would have to conduct him or herself in a manner likely to demonstrate to his employer loyalty, good faith and cooperation. Against this background, the recent case of Moyo v Old Mutual (22791/2019) [2019] ZAGPJHC 229 (30 July 2019) (Moyo) demonstrates the impact of a breach of the implied duty to preserve mutual trust and confidence on the employment relationship. This case note intends to examine the implied obligation that rests upon the employer to safeguard trust and confidence in the relationship. The case note further reflects on the implied duty of employees to safeguard and protect mutual trust and confidence. After all, trust forms the basic fundamental core of the employment relationship, and any breach of this duty is likely to result in an irretrievable breakdown of the employment relationship. Once there is a breakdown of trust and confidence, it remains a mammoth task to restore the relationship.